LITERATURE REVIEW MODUL PEMBELAJARAN BERBASIS AI UNTUK MENINGKATKAN KETERAMPILAN MENGAJAR GURU SMK - Yusep Windhu Ari Wibowo; Ali Murtopo; Dian Puspita Sari; Muhammad Fadli (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
The challenge faced in developing AI modules is that teachers find it difficult to understand the basic concepts of AI and how to implement it in learning. This research aims to develop an AI-based learning module for use by English teachers in vocational schools. This research uses the literature review method on AI-based learning. The researcher collected data from various national and international journals. The results of this study provide an overview of the application of AI in education. There are five main recommendations for the development of AI-based learning modules. First, the involvement of teachers is very important so that the module matches the real needs in the field. Second, the module needs to be designed to suit the various learning styles of students through a personalized and adaptive approach. Third, collaboration between schools and technology developers is needed so that the module is in line with the curriculum and can be implemented well. Fourth, regular evaluation and monitoring are needed to continuously improve the quality of the module. Fifth, an awareness campaign is needed to encourage the wider use of AI in education.